Priority directions for increasing diversification of the regional economy - M. M. Avezova; M. G. Mansurova (Управление)
The article considers the issues of increasing the level of economic diversification as an effective direction for achieving the strategy of sustainable development of the region. The paper carries out the analysis of the current state of the economy of the Sughd region of the Republic of Tajikistan, calculates the sectoral indicators of diversification and the average level of diversification of the regional economy. An assessment based on the existing methodology showed the need to continue the diversification process, but does not indicate which industries should be diversified first.In order to identify priority sectors in carrying out diversification, a ranking matrix for economic sectors has been developed. The diversification coefficients and the structural coefficient were used as indicators in the matrix, which makes it possible to assess the existing level of diversification of the region’s industries and determine the priority sectors (trade, agriculture and industry), which have the necessary economic potential.The article also considers the experience of successful countries that have reached a high level of economic development as a result of increasing the level of diversification, on the basis of which recommendations for the Sughd region of Tajikistan are substantiated in order to achieve sustainable regional economic growth. The research results can be used in the processes of developing a strategy for the development of the country’s regions and state regulation of spatial development.